Pengaruh Penerapan Metode Pembelajaran Lattice Terhadap Hasil Belajar Matematika Peserta Didik - Resky Ayu; Lisa Aditya Dwiwansyah Musa (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2020)
This study aimed to determine the effect of lattice learning methods on mathematics learning outcomes on the integer multiplication operation for the grade VII students of SMPN 2 Bua. This is a pre-experimental research design that uses a one-group pretest-posttest research design type. The instrument used a description test consist of 3 questions. The samples were students of class VII A of SMPN 2 Bua. The analysis result of the two-tailed curve, Ha was accepted, and Ho was rejected. The conclusion was a significant influence on the lattice learning method on mathematics learning outcomes in the integer for grade VII students of SMPN 2 Bua. So, a successful student not only by learning theory but also by the right learning methods. The results of this study will be able to help teachers to improve student learning outcomes.